Oral Tolerance Induced by Heat Shock Protein 65-Producing Lactococcus lactis Mitigates Inflammation in Leishmania braziliensis Infection - Guerra, Priscila Valera; Andrade, Camila Mattos; Nunes, Ivanéia Valeriano; Gama, Brena Cardoso; Tibúrcio, Rafael; Santos, Washington Luis Conrado; Azevedo, Vasco Ariston; Tavares, Natalia Machado; Rebouças, Juliana de Souza; Maiolii, Tatiani Uceli; Faria, Ana Maria Caetano; Brodskyn, Cláudia Ida (Frontiers in Immunology, 2021)
Cutaneous leishmaniasis caused by L. braziliensis induces a pronounced Th1 inflammatory response characterized by IFN-γ production. Even in the absence of parasites, lesions result from a severe inflammatory response in which inflammatory cytokines play an important role. Different approaches have been used to evaluate the therapeutic potential of orally administrated heat shock proteins (Hsp). These proteins are evolutionarily preserved from bacteria to humans, highly expressed under inflammatory conditions and described as immunodominant antigens. Tolerance induced by the oral administration of Hsp65 is capable of suppressing inflammation and inducing differentiation in regulatory cells, and has been successfully demonstrated in several experimental models of autoimmune and inflammatory diseases. We initially administered recombinant Lactococcus lactis (L. lactis) prior to infection as a proof of concept, in order to verify its immunomodulatory potential in the inflammatory response arising from L. braziliensis. Using this experimental approach, we demonstrated that the oral administration of a recombinant L. lactis strain, which produces and secretes Hsp65 from Mycobacterium leprae directly into the gut, mitigated the effects of inflammation caused by L. braziliensis infection in association or not with PAM 3CSK4 (N-α-Palmitoyl-S-[2,3-bis(palmitoyloxy)-(2RS)-propyl]-L-cysteine, a TLR2 agonist). This was evidenced by the production of anti-inflammatory cytokines and the expansion of regulatory T cells in the draining lymph nodes of BALB/c mice. Our in vitro experimental results suggest that IL-10, TLR-2 and LAP are important immunomodulators in L. braziliensis infection. In addition, recombinant L. lactis administered 4 weeks after infection was observed to decrease lesion size, as well as the number of parasites, and produced a higher IL-10 production and decrease IFN-γ secretion. Together, these results indicate that Hsp65-producing L. lactis can be considered as an alternative candidate for treatment in both autoimmune diseases, as well as in chronic infections that cause inflammatory disease.